TEJAMLILIK – TRANSPOZITSIYANI YUZAGA KELTIRUVCHI OMIL SIFATIDA (Usmon Azim she’riyati misolida) - Islamova, D. (SCIENCE and SOCIETY, 2020)
The author of the article analyzes the aspects of transformation as a result of speech economy of transpositive words, which were used in the language of lyrical poetry of the national poet of Uzbekistan Usman Azim.
Keywords: transposition; conversion; lexeme; economy; brevity; compactness; accuracy and durability